Case Report: A Case of Locally Advanced Pancreatic Cancer Which Achieved Progression Free for Over 12 Months by Subsequent Therapy with Anlotinib Hydrochloride Plus Tegafur-Gimeracil-Oteracil Potassium (TS-1) - Luo, Dongcheng; Liao, Sina; Li, Qian; Lin, Youzhi; Wei, Junbao; Li, Yongqiang; Liao, Xiaoli (Frontiers in Oncology, 2022)
Titled the “most destructive of all cancers”, pancreatic cancer is a malignant tumor with a very poor prognosis and has a poor response to systemic therapy. At present, several studies have shown that tegafur-gimeracil-oteracil potassium (hereinafter referred to as TS-1) is no less superior to gemcitabine in the treatment of advanced pancreatic cancer. In addition, a number of current clinical studies have shown that targeted therapy combined with chemotherapy reflects therapeutic advantages in pancreatic cancer. Moreover, in vitro and in vivo experiments have also demonstrated that anlotinib can curb the proliferation of pancreatic cancer cells and induce their apoptosis. Here, we report for the first time that a patient with locally advanced pancreatic cancer achieved good efficacy after switching to TS-1 chemotherapy combined with anlotinib targeted therapy. Previously, the disease of the patient still rapidly progressed without control following the first switch to abraxane combined with gemcitabine chemotherapy (AG regimen) due to the progression after chemo-radiotherapy. In this case, the patient achieved progression-free survival (PFS) of over 14 months via the treatment with anlotinib targeted therapy combined with TS-1 chemotherapy and secondary radiotherapy (prior to secondary radiotherapy, the patient achieved a PFS of nearly 12 months via the treatment with oral anlotinib combined with TS-1). Up to now, the progress of the disease is ceased. The oral administration of targeted therapy and chemotherapy are still in progress and the general condition of the patient is good. This suggests that patients with advanced pancreatic cancer may benefit from treatment with the anlotinib targeted therapy combined with TS-1 chemotherapy.